Immunoglobulin IgG, IgM and IgA concentrations in the blood serum in women with adenemyosis after hysterectomy - Sikora, Wacław (Menopause Review/Przegląd Menopauzalny, 2003)
Objectives: Surgery is traumatic for the body and can both stimulate or suppress its immune system. Most common major surgery (second to caesarean section) performed in gynaecological – obstetric wards is hysterectomy. The purpose of the research was to compare the concentration of immunoglobulines IgG, IgM, IgA, gamma globulin fraction and blood serum total protein in pre-, early and late phase of period postoperative in women who underwent intrafascial hysterectomy with or without adnexa. Materials and methods: The study covered 27 patients with uterine endometriosis, aged 49.5 years (±9,6) who underwent surgery in gynaecological – obstetric ward, SP ZOZ Lipsko in 1999–2001. The blood was drawn before treatment, on 1st, 10th and on 30th day following the surgery. Results: Following hysterectomy (1st day), a statistically significant increase in the level of IgG, IgM, IgA immunoglobulin and blood serum total protein. Conclusions: 1. Hysterectomy inductes a change in constellation of protein in blood serum, which manifests in decreased concentration of IgG, IgM, IgA and blood serum total protein. 2. Prior the surgery concentrations IgG and IgM concentration was not highest in women with uterine endometriosis.